[tex]c)\\\\ 3,7-4\frac{2}{5}=3\frac{7}{10}-4\frac{2}{5}=3\frac{7}{10}-4\frac{ 4}{10}=3\frac{7}{10}-3\frac{14}{10}= -\frac{7}{10}=-0,7\\\\ -\frac{7}{8}+(-0,7)=-\frac{7}{8}-\frac{7}{10}=-\frac{35}{40}-\frac{28}{40}=-\frac{63}{40}=-1\frac{23}{40}= -1,575 \\\\1,4-(-1\frac{3}{4})=1 \frac{4}{10}+1\frac{3}{4}=1 \frac{8}{20}+1\frac{15}{20}=2\frac{23}{20}=3 \frac{3}{20}=3,15\\\\-2\frac{1}{6}-(-1,6)= -2\frac{1}{6}+ 1 \frac{6}{10}= -2\frac{ 5}{30}+ 1 \frac{18}{30}= -1\frac{ 35}{30}+ 1 \frac{18}{30}=-\frac{34}{30}=-\frac{17}{30}[/tex]